Parvovirus B19-associated purpureo-petechial exanthema. Differential diagnosis with non-infectious vasculitis - S. V. Haliullina; V. A. Anohin; I. Ya. Lutfullin; D. E. Dolgovskova; O. A. Nazarova (Журнал инфектологии, 2024)
Clinical manifestations of parvovirus B19 infection are varied and depend on the age, hematological and immune status of the infected person. Classic manifestations of the disease include infectious erythema in children, arthritis/ arthralgia in adults, severe anemia in patients with impaired erythropoiesis and nonimmune hydrops fetalis in case of intrauterine infection. In addition, various types of exanthema associated with parvovirus B19 have been described. These include “papularpurpuric gloves and socks syndrome, PPGSS”, “purpuropetechial rash associated with parvovirus B19, PAPPE”, “acropethechial syndrome”, “asymmetric periflexural exanthema of children”, etc. In all cases, skin manifestations are characterized by a hemorrhagic rash. A certain difficulty is the differential diagnosis of such variants of parvovirus B19 infection with vasculitis of noninfectious origin, primarily with the most common IgA vasculitis (HenochSchonlein purpura) and cutaneous small vessel vasculitis (CSVV). The connection of vasculitis with infection in some cases is obvious and is confirmed by epidemiological observations. Infections can act as a trigger for the development of vasculitis or be its direct cause (vasculitis in this case can be classified as “vasculitis associated with a probable etiology” in the nomenclature system of the Chapel Hill Consensus Conference 2012). Considering that the nature of vasculitis is not completely clear, the question of a possible connection between their occurrence and infection with PVB19 requires further study. From a clinical point of view, the differential diagnosis of hemorrhagic exanthema associated with PVB19 and vasculitis is extremely important primarily because of the need for immediate treatment of the latter. From an epidemiological point of view, this is important, since patients with PPGSS or PAPPE are infectious throughout the period of the rash.Apparently, additional studies, primarily histological, of a sufficient number of samples from patients with purpuricpetechial rash and serologically proven acute parvovirus B19 infection will help solve this problem.